An Innovative High Frequency Hyperthermia Approach against SARS-Cov-2 and Related Virus: Feasibility Analysis - Cutolo, Maria Alessandra; Migliaccio, Antimo; Altucci, Lucia; Cutolo, Antonello; Cusano, Andrea (Archives of Clinical and Biomedical Research, 2021)
Heating is a strong enemy of SARS-CoV and related virus. Starting from both this consideration and from the basic principle of the microwave ovens which are based on the strong absorption, from organic tissues, of the radiation centered around 2.15 GHz, we examine the feasibility of using this frequency range to both lower the strength of the SARS-CoV (and related virus) inside the human body and to easily sterilize objects or closed rooms. This is only a preliminary theoretical feasibility analysis, which, of course, should be experimentally tested.